Explicating audience engagement with political debates: a content analysis of the digital debate about youth unemployment on Daily Thetha Facebook page. - Mohale, Mphela Precious (My University, 2023)
This study aims to explore the ways that young audiences of the television talk show Daily Thetha, interpret and construct meanings of political messages communicated on the show. The study seeks to achieve this by exploring the digital engagement patterns of audiences on the Daily Thetha Facebook page. The political topic chosen for the study is youth unemployment. For analysis purposes, the study uses five Daily Thetha episodes which discussed different facets of youth unemployment. The research questions central to this study are explored by analysing Facebook posts created for the episodes, as well as the comments under each post. The research data is analysed through content analysis. Both manifest and latent content analyses are used for data analysis. Research findings are presented and discussed using both qualitative and quantitative methods. Television talk shows are a site for public discussions and the formation of public opinion. Habermas’ public sphere is a theoretical basis for debates and the formation of public discourse about societal issues. The freedom of the press as well as the freedom of expression of ideas are vital for democracy and are enshrined in the South African Bill of Rights. The media play a vital role in promoting and sustaining democracy in South Africa. The study based on how the television talk show Daily Thetha influences public debate among its young audiences is thus important to explore. Moreover, media audiences are heterogenous, thus, interpreting and engaging with media texts differently. Findings from this study demonstrated that Daily Thetha digital audiences can be classified as both active and passive readers. Moreover, findings also show that Daily Thetha Facebook page is characterised as a digital sub-public sphere and can be classified as a political, literal as well as a public cultural public sphere.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Arts to the Faculty of Humanities, School of Literature, Language and Media, University of the Witwatersrand, Johannesburg, 2023